Kinerja Dinas Sosial dalam Penanganan Gelandangan dan Pengemis (GEPENG) Di Kota Denpasar - Damayanti, Ni Komang Kristina; Yudartha, I Putu Dharmanu; Wismayanti, Kadek Wiwin Dwi (CITIZEN CHARTER; Vol 2 No 1 (2022): Administrasi Publik 2022, 2022)
Efforts to deal with sprawl by the Denpasar City Social Agency have been carried out since 2015 until now, but there are still many problems that have not been resolved, therefore it is necessary to measure the performance of public organizations to review how the performance of the Social Service in handling sprawl in Denpasar City. This study uses a qualitative research type with a descriptive approach. Informant Determination Techniques in this study using purposive sampling. Based on this research study using the theory of performance measurement of public organizations according to Dwiyanto in Pasolong (2014: 178-179). The results showed that the performance of the Social Service in handling sprawl in Denpasar City was quite good. Keywords: Performance, Denpasar City Social Agency, Homeless and Beggars